2018
DOI: 10.1155/2018/1372359
|View full text |Cite
|
Sign up to set email alerts
|

A Probability Distribution for Quantum Tunneling Times

Abstract: We propose a general expression for the probability distribution of real-valued tunneling times of a localized particle, as measured by the Salecker-Wigner-Peres quantum clock. This general expression is used to obtain the distribution of times for the scattering of a particle through a static rectangular barrier and for the tunneling decay of an initially bound state after the sudden deformation of the potential, the latter case being relevant to understand tunneling times in recent attosecond experiments inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Importantly, Winful showed that the contribution of the first term is disentangled from the barrier time delay[13]. And in their work Lunardi et al used the so-called Salecker-Wigner-Peres quantum-clock (SWP-QC) with MC-simulation[14,15], they found that the tunneling time in the attoclock is given by the form 6. The first term, called well-time, is according to the authors the time delay spent before reaching the barrier and the second term corresponds to the barrier time delay.…”
mentioning
confidence: 99%
“…Importantly, Winful showed that the contribution of the first term is disentangled from the barrier time delay[13]. And in their work Lunardi et al used the so-called Salecker-Wigner-Peres quantum-clock (SWP-QC) with MC-simulation[14,15], they found that the tunneling time in the attoclock is given by the form 6. The first term, called well-time, is according to the authors the time delay spent before reaching the barrier and the second term corresponds to the barrier time delay.…”
mentioning
confidence: 99%
“…If the interparticle distance between the particles of the secondary phase is small enough, tunneling paths form and electrons move between the conductive particles [76]. However, when the interparticle distance increases, the probability for tunneling paths to form decreases [77]. For larger interparticle distance, the percolation theory is dominant.…”
Section: Resistive Sensors For Detecting Multiples Stimulimentioning
confidence: 99%
“…Though a direct measurement of such small times is difficult, the advent of intense laser fields has made measurements [13][14][15] on the tunneling of bound electrons [16] from atoms possible. In this field ionization process, the electron tunnels through the potential created by a superposition of the atomic Coulomb potential and the laser field.…”
Section: Introductionmentioning
confidence: 99%